1980
DOI: 10.1083/jcb.86.1.181
|View full text |Cite
|
Sign up to set email alerts
|

Formation of multinuclear cells induced by dimethyl sulfoxide: inhibition of cytokinesis and occurrence of novel nuclear division in Dictyostelium cells.

Abstract: Our previous studies showed that 10% dimethyl sulfoxide (DMSO) induces the formation of actin microfilament bundles in the cell nucleus together with the dislocation of cortical microfilaments from the plasma membrane . The present study investigated the effects of DMSO on diverse activities mediated by cellular microfilaments as the second step toward assessing potential differences between nuclear and cytoplasmic actins of Dictyostelium mucoroides. DMSO was found to reversibly inhibit cell-to-glass as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1983
1983
1990
1990

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Since finding the prominent effect of DMSO of inducing nuclear actin bundle formation (15,16), we have performed some studies on cell motility by using this agent as a chemical probe with which to manipulate the cellular microfilaments (17,18). Our preliminary finding that the cortical microfdaments became dislocated from the plasma membrane by the action of DMSO encouraged us to do the present study to gain insight into the supramolecular mechanism of cell motile activities.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Since finding the prominent effect of DMSO of inducing nuclear actin bundle formation (15,16), we have performed some studies on cell motility by using this agent as a chemical probe with which to manipulate the cellular microfilaments (17,18). Our preliminary finding that the cortical microfdaments became dislocated from the plasma membrane by the action of DMSO encouraged us to do the present study to gain insight into the supramolecular mechanism of cell motile activities.…”
Section: Discussionmentioning
confidence: 97%
“…Previously, we have shown that DMSO acts on Dictyosteliurn cells to dislocate the cortex microfflaments from the plasma membrane, resulting in cell rounding up and a cessation of cytoplasmic streaming (17). We have also revealed that 5% DMSO impedes the cytokinesis of this organism in a growing condition and that conspicuous multinuclear cells are produced (18). In this study, we used DMSO as a chemical agent to manipulate the microftlament system of the cortex layer to assess its possible roles in cell structure and motile activities.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The possible role of myosin during mitosis has been debated for many years. Because the disruption of the mhcA gene gives rise to a population of multinucleated cells, we were interested m study whether the multinucleation results from normal mitosis (30) or from abnormal nuclear division (18). We found that the hmm cells were capable of forming spindles.…”
Section: Physiological Propertiesmentioning
confidence: 99%
“…(DMSO), frequently used as a solvent for water-insoluble drugs, is known to have effects on the cytoskeletal proteins. When included in culture medium, it causes the disappearance of cortical microfilaments and the formation of actin bundles in the nucleus, leading to cessation of cytokinesis and cell division (4)(5)(6)19). DMSO also induces the in vitro assembly of tubulin in the absence of associated proteins and stabilises the polymerised microtubules (8,18).…”
mentioning
confidence: 99%